1997
DOI: 10.1093/treephys/17.7.467
|View full text |Cite
|
Sign up to set email alerts
|

Crop load and water stress effects on daily stem growth in peach (Prunus persica)

Abstract: We investigated crop load and water stress effects on diurnal stem extension growth of field-grown peach (Prunus persica (L.) Batsch) trees. Neither the presence of fruit nor reduced irrigation significantly altered the timing of diurnal fluctuations in stem growth rate. Stems with subtending fruit had significantly reduced growth compared to stems with no subtending fruit. Crop load had no significant effect on relative stem extension rates and the majority of the reduction in absolute growth was the result o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 35 publications
(37 reference statements)
2
17
1
Order By: Relevance
“…Lauri et al (1996) suggested that, unless it is excessive, increased vegetative growth tends to promote flowering and fruit development. On the other hand it has been shown in certain fruit crops that an increase in fruiting is correlated with shorter bearing shoots (Berman and DeJong 1997). It should be pointed out that the relationships between fruit yield and shoot length in the present study were based on the 1-yr-old shoots, not bearing shoots.…”
Section: Discussioncontrasting
confidence: 55%
“…Lauri et al (1996) suggested that, unless it is excessive, increased vegetative growth tends to promote flowering and fruit development. On the other hand it has been shown in certain fruit crops that an increase in fruiting is correlated with shorter bearing shoots (Berman and DeJong 1997). It should be pointed out that the relationships between fruit yield and shoot length in the present study were based on the 1-yr-old shoots, not bearing shoots.…”
Section: Discussioncontrasting
confidence: 55%
“…This is not surprising and in accordance with previous findings, not only on peaches, showing that a lower crop load releases fruit competition for resources and induces higher growth rates in the remaining fruits (Burge et al, 1987;DeJong and Grossman, 1995;Berman and DeJong, 1997;Miras-Avalos et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…In our dataset, flowering occurrence after a minimum number of nodes can also be interpreted with respect to alternate flowering which is a specificity of perennial plants resulting from the absence of flowering induction in particular years. The particular status of flowering in tree ontogeny may arise from the high carbon cost of flower and fruit production (Bustan and Goldschmidt 1998) and competition with current vegetative growth (Cannell 1985;Berman and DeJong 1997). The terminal position of flowering and subsequent sympodial branching may also be involved in the reduction in vegetative growth since they induce a rupture in vascular connections and probably in hydraulic conductance, and this is assumed to be responsible for age-related decline in trees (Martinez-Vilalta et al 2007).…”
Section: Discussionmentioning
confidence: 99%